Traumatic Stress in South Africa - Kaminer, Deborah (Wits University Press, 2010)
Taking both a historical and contemporary perspective, the book covers the extent of and manner in which traumatic stress manifests, including the way in which exposure to such extremely threatening events impacts on people's meaning and belief systems. Therapeutic and community strategies for addressing and healing the effects of trauma exposure are comprehensively covered, as well as the particular needs of traumatised children and adolescents. Illustrative case material is used to render ideas accessible and engaging. The book also provides a comprehensive and up-to-date overview of theory and practice in the field of traumatic stress studies, incorporating both international and South African specific findings.